REACTIVITIES OF SOME ALDOSES TOWARDS IODINE IN ALKALINE AQUEOUS MEDIUM - Azmat, R.; Nizami, S. S. (The Nucleus, 2020)
The kinetics studies of oxidation of some reducing sugars by aqueous alkaline solution of iodine investigated. Results demonstrated that iodine in the presence of alkali converted into hypoiodous acid which was effective oxidizing species. Reaction between iodine and sugars was slowest reaction. The rate of oxidation of sugars was affected by change in pH of the medium and maximum at pH 11.4 where the concentration of hypoiodous acid was maximum which oxidized the sugars into respective acids. The rate of oxidation followed first order kinetics with respect to substrate and obeyed zero order kinetics with that of iodine. Change in ionic strength of the medium showed no effect on the rate of oxidation indicating that reaction occured between molecular species and there was no ionic species present in the rate determining step. Reaction was affected by the change in temperature and value of energy of activation corresponding to glucose, galactose, D-mannose and L-arabinose were 10.16 kJ/mol, 12.17 kJ/mol, 14.00 kJ/mol and 20.22 kJ/mol respectively.